Pengaruh Viralitas Produk dan Persepsi Halal Terhadap Keputusan Pembelian Telur Balut Oleh Mahasiswa Muslim di Surabaya - Dinda Novalin Sutrisno Putri (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study aims to analyze the influence of product virality and halal perception on purchasing decisions for balut eggs by Muslim students in Surabaya. The phenomenon of extreme food virality on social media has increased consumer curiosity, but on the other hand, it has given rise to strong halal considerations for Muslim consumers. This study used a quantitative approach with primary data obtained through an online questionnaire distributed to Muslim students in Surabaya. The sampling technique used purposive sampling with a total of 104 respondents. Data analysis was conducted using multiple linear regression with the help of SPSS version 25. The results showed that product virality had a positive and significant effect on purchasing decisions for balut eggs, while halal perception had a negative and significant effect on purchasing decisions. Simultaneously, product virality and halal perception had a significant effect on purchasing decisions. These findings indicate that although virality can drive purchasing interest, halal considerations remain a dominant factor in shaping Muslim students' consumption decisions. This study is expected to provide academic contributions to the study of Muslim consumer behavior and provide practical considerations for viral food businesses to pay attention to the halal aspects of their products.